2017
DOI: 10.1186/s12906-017-1700-9
|View full text |Cite
|
Sign up to set email alerts
|

The immune-regulating effect of Xiao’er Qixingcha in constipated mice induced by high-heat and high-protein diet

Abstract: BackgroundXiao’er Qixingcha (EXQ) has been extensively applied to relieve dyspepsia and constipation in children for hundreds of years in China. However, the therapeutic mechanism underlying its efficacy remained to be defined. The present study aimed to clarify the possible laxative and immune-regulating effects of EXQ on two models of experimental constipation in mice, which mimicked the pediatric constipation caused by high-heat and high-protein diet (HHPD).MethodsThe two models of constipated mice were ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…We examined intestinal epithelial information employing H&E staining ( Figure 2A ). First of all, alterations in thicknesses of the colonic mucosa, submucosal, and muscle layer were analyzed ( Qu et al, 2017 ). The results showed that the layered muscle structure of the mouse colon under constipation status became thicker ( Figure 2B , n = 9, p < 0.001), which is markedly reduced after the treatment constipation model with rhubarb extract ( Figure 2B , n = 9, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…We examined intestinal epithelial information employing H&E staining ( Figure 2A ). First of all, alterations in thicknesses of the colonic mucosa, submucosal, and muscle layer were analyzed ( Qu et al, 2017 ). The results showed that the layered muscle structure of the mouse colon under constipation status became thicker ( Figure 2B , n = 9, p < 0.001), which is markedly reduced after the treatment constipation model with rhubarb extract ( Figure 2B , n = 9, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…2A). First of all, alterations in thicknesses of the colonic mucosa, submucosal, muscle layer were analyzed (23). The results showed that the layered muscle structure of the mouse colon under constipation status became thicker (Fig.…”
Section: Results2 Alterations Of Histopathological and Cytological St...mentioning
confidence: 99%
“…By detection of some indexes of immunity, we found that the 5P had significant effects on improvement of immunity compared with CTX. Moreover, some studies have suggested that antioxidants and immune function are both essential for cancer prevention [ 24 ]. Based on the results of 5P treatment in H22 tumor-bearing mice, we concluded that 5P could reduce the damage produced caused by free radicals and protect normal tissues in H22 tumor-bearing mice through the following mechanisms.…”
Section: Discussionmentioning
confidence: 99%